Effectiveness of a Web‐Based Personalized Rheumatoid Arthritis Risk Tool With or Without a Health Educator for Knowledge of Rheumatoid Arthritis Risk Factors. Issue 10 (27th September 2018) - Prado, Maria G.; Iversen, Maura D.; Yu, Zhi; Miller Kroouze, Rachel; Triedman, Nellie A.; Kalia, Sarah S.; Lu, Bing; Green, Robert C.; Karlson, Elizabeth W.; Sparks, Jeffrey A.
Abstract : Objective: To assess knowledge of rheumatoid arthritis (RA) risk factors among unaffected first‐degree relatives (FDRs) and to study whether a personalized RA education tool increases risk factor knowledge. Methods: We performed a randomized controlled trial assessing RA educational interventions among 238 FDRs. The web‐based Personalized Risk Estimator for RA (PRE‐RA) tool displayed personalized RA risk results (genetics, autoantibodies, demographics, and behaviors) and educated about risk factors. Subjects were randomly assigned to a Comparison arm (standard RA education; n = 80), a PRE‐RA arm (PRE‐RA alone; n = 78), or a PRE‐RA Plus arm (PRE‐RA and a one‐on‐one session with a trained health educator; n = 80). The RA Knowledge Score (RAKS), the number of 8 established RA risk factors identified as related to RA, was calculated at baseline and post‐education (immediate/6 weeks/6 months/12 months). We compared RAKS and its components at each post‐education point by randomization arm. Results: At baseline before education, few FDRs identified behavioral RA risk factors (15.6% for dental health, 31.9% for smoking, 47.5% for overweight/obesity, and 54.2% for diet). After education, RAKS increased in all arms, higher in PRE‐RA and PRE‐RA Plus than Comparison at all post‐education points ( P < 0.05). PRE‐RA subjects were more likely to identify risk factors than those who received standard education (proportion agreeing that smoking is a risk factor at 6 weeks: 83.1% in the PRE‐RA Plus arm, 71.8% in the PRE‐RA arm, and 43.1% in the Comparison arm; P < 0.05 for PRE‐RA versus Comparison). Conclusion: Despite being both familiar with RA and at increased risk, FDRs had low knowledge about RA risk factors. A web‐based personalized RA education tool successfully increased RA risk factor knowledge.